Brazilian dustywings (Neuroptera: Coniopterygidae): new species of Incasemidalis Meinander, 1972 and Coniopteryx Curtis, 1834, checklist and key for the Brazilian species - Martins, Caleb C.; Amorim, Dalton De Souza (Zootaxa, 2016)
Two subfamilies and three genera of Coniopterygidae have been reported to date for Brazil, with a total of 44 of species. In this paper two new Brazilian species are described from the genera Coniopteryx Curtis, 1834 and Incasemidalis Meinander, 1972—C. (Scotoconiopteryx) letardii sp. n. and Incasemidalis brasiliensis sp. n. —increasing the number of reported genera for Brazil to four and the number of Brazilian species to 46. This is the first report of Incasemidalis for Brazil. Moreover, in the case of C. (C.) callangana Enderlein, 1906, C. (Scotoconiopteryx) flinti Meinander, 1975, C. (S.) tucumana Navás, 1930, Semidalis nimboiformis Monserrat, 1989 and S. normani Meinander, 1982 some additional characteristics are given to the original descriptions or earlier redescriptions, with new records increasing their known distribution. An updated checklist of the Coniopterygidae from Brazil is provided, as well as a key for the Brazilian species of the family.